Interpupillary Distance and Pupil Diameter of Baseball Athletes and Non-athletes. - Hunfalvay, Melissa; Kubitz, Karla; Murray, Nicholas P.; Tibbert, Stephanie; Bolte, Takumi (Optometry & Visual Performance, 2018)
Purpose: To examine whether differences exist in interpupillary distance (IPD) and pupil diameter (PD) between professional baseball players compared to non-athletes (males and females). Methods: 149 Major League Baseball (MLB) athletes and 416 non-athletes (NA) were examined on the RightEye IPD/PD test. One-way analysis of variance with Levene tests for testing assumption of variances were performed. If assumptions were violated, the Kruskal-Wallis test was used to analyze group differences with Tukey and Dunnett (T3) post-hoc tests. Alpha was set to p<0.05. Results: For IPD, there was a significant difference (p<0.0005) between female non-athletes, male non-athletes, and MLB players. IPD did not meet the assumption of homogeneity of variance (p<0.0005). Post-hoc tests indicated that for IPD, all three groups were significantly different from one another. Female non-athletes had the smallest IPD. Male nonathletes had a larger IPD than female athletes. MLB players had the largest IPD. For PD, there was a significant difference (< 0.0005) between female non-athletes, male non-athletes, and MLB players. Post-hoc tests indicated that for PD, male and female non-athletes were not significantly different from one another. MLB players were, however, significantly different from female non-athletes and from male non-athletes. Both male and female non-athletes had a larger PD than MLB players. Conclusions: Past research has shown that IPD and PD affect important visual skills needed for playing baseball, such as stereo acuity, convergence, accommodation, and image quality. Differences in IPD and PD may provide another component in the equation that determines success.